Chemical and Biological Characteristics of Whole Crop Corn Silage with Rice Bran and White Cabbage Additives during Ensilage - Ridla, Muhammad; Martin, Rima Shidqiyya Hidayati; Jayanegara, Anuraga; Muis, Nurmaya Rahmawati; Nahrowi, Nahrowi (Universitas Halu Oleo, 2022)
ABSTRACT The objective of this work was to evaluate whole crop corn silage quality throughout the ensilage periods with rice bran and white cabbage as additives. Whole crop corn from 60 days aged was chopped ±2-5 cm, and added rice bran, white cabbage and without additive (control) then put on plastic bag under anaerobic condition for 1, 2, 3, and 4 weeks. Silages were analyzed in physical characteristics (flavor, color, texture); chemical characteristics (dry matter/DM, DM recovery, organic matter/OM, pH value, fleigh value, water-soluble carbohydrate/WSC), and biological characteristics (type and number of lactic acid bacteria (LAB)) weekly. The results showed that additives affected (p